2019
DOI: 10.1016/j.mtcomm.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide-releasing LLDPE films as greenhouse cover materials

Abstract: The use of chemical pesticides is limited by several public health concerns regarding their toxicity levels and indiscriminate use. Nevertheless, they are still vital components of agricultural industry since no other competitive equivalents to chemical pesticides still exist in terms of efficiency. This study describes the preparation and biological assessment of an insecticide releasing plastic film for agricultural covering purposes. The formulation was prepared by incorporation of deltamethrin loaded, nano… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Sustainability concerns in crop production and the need for ideal pest control management systems and organic cultivation [15] have informed the development of greenhouse materials with customized properties such as higher photo-selectivity and slow insecticide release capabilities [32,33]. Other properties associated with modern greenhouse materials are limited droplet formation, reduced heat losses, accumulation of dust, and transmission of a particular wavelength of light [14,31,32,34].…”
Section: Properties Of Greenhouse Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustainability concerns in crop production and the need for ideal pest control management systems and organic cultivation [15] have informed the development of greenhouse materials with customized properties such as higher photo-selectivity and slow insecticide release capabilities [32,33]. Other properties associated with modern greenhouse materials are limited droplet formation, reduced heat losses, accumulation of dust, and transmission of a particular wavelength of light [14,31,32,34].…”
Section: Properties Of Greenhouse Materialsmentioning
confidence: 99%
“…The Chinese prefer fired clay blocks and compacted clay as shown in Figure 1 [21] while the construction of greenhouse walls and roofs using one material such as glass or plastic films and sheets is common in other countries [14,34,36]. Zhang and co-researchers reported low conductivity in the clay bricks constructed with agricultural waste (0.280 W m −1 k −1 ) compared to porous clay blocks.…”
Section: Impact Of North Wall Materials For Chinese-type Greenhouses mentioning
confidence: 99%
See 1 more Smart Citation
“…The main challenge is to achieve similar capabilities using bio-based polymer films/covers. The data reported by Antón, Torrellas, Raya, and Montero [39] and Seven, Tastan, Tas, Ünal, and Ince [40] is based on polycarbonate and LLDPE films, which are not biodegradable. However, the degradation process can be augmented by UV light and oxidizing agents [41].…”
Section: Plastic Covers/films For Greenhousesmentioning
confidence: 99%
“…Therefore, to minimise the incorporation of the pesticide residues into food and water cycle, extensive research on controlled release formulation (CRF) of agrochemicals has been reported in the previous studies (Kah and Hofmann 2014;Cao et al 2019;Seven et al 2019;Song et al 2019;Tang et al 2019;Wani et al 2019). The pesticide with CRF was fabricated by incorporating or intercalating the pesticide into a host material which acts as a carrier for the pesticide (Bugatti et al 2019;Rebitski et al 2019;Sarijo et al 2019;Wang et al 2019).…”
Section: Introductionmentioning
confidence: 99%